Organisational responses to alleged scientific misconduct: Sensemaking, sensegiving, and sensehiding. (4th December 2018) - Horbach, Serge P J M; Breit, Eric; Mamelund, Svenn-Erik
Abstract: While a substantive literature has emerged on the prevalence, causes, and consequences of scientific misconduct, little is known about the organisational perspective in cases of (alleged) misconduct. We address this knowledge gap by employing a comparative case study approach to describe and assess the handling of four cases of alleged misconduct by their university, respectively in the Netherlands and Norway. We propose a theoretical model that explains how organisational responses to misconduct emerge and evolve as iterations of the processes of sensemaking, sensegiving, and sensehiding. In addition, we link these iterations to a set of background premises that nurture the organisational responses and to the responses' outcomes and consequences. We conclude that several aspects of the organisational responses hinder effective learning processes within organisations and their members. Our analysis provides fruitful heuristics for organisations to reflect on, or plan their response strategies to allow for optimal learning.